A Humboldtian critique of the University of the Philippines as the flagship of Philippine higher education (part I) - Demeterio, Feorillo Petronilo A. (Animo Repository, 2018)
For the Philippines to benefit from the ASEAN integration and globalization, in general, it must be able to mold highly educated citizens who can proactively engage themselves with the national, regional, and international knowledge economies.1 The Philippines has nine research universities that presumably lead its approximately 2,500 higher educational institutions in molding these needed citizens. These nine research universities are the eight autonomous constituent units of the University of the Philippines and De La Salle University. The idea of the modern research university was invented more than 200 years ago in Berlin by the philosopher, linguist, humanist, and statesman Wilhelm von Humboldt (1767-1835). Around 1850, American educational leaders started to appropriate Humboldt's ideas to establish the American research universities. As the University of the Philippines is an American creation and at the same time the flagship institution of Philippine higher education, this paper used the Humboldtian philosophy of education, as well as its American rendition, in looking at the soundness of this university's claim to be a research university. To attain this goal this paper has three substantive sections: 1) a discussion on Humboldt's philosophy of education, 2) a discussion on the American translation of Humboldt's philosophy of education, 3) a critique of the foundational principles of the University of the Philippines as a research university. © 2018 F.P.A. Demeterio III and Roland Theuas DS. Pada.